Подготовка специалистов паро- и газотурбинистов в Киевском политехническом институте (конец XIX–XX вв.) - Христич, А. С.; Татарчук, В. В. (НТУ "ХПИ", 2013)
В статье рассказывается про историю подготовки в Киевском политехническом институте специалистов по паровым и газовым турбинам (конец ХІХ–ХХ вв.): подготовку инженерных и научно-педагогических кадров, научно-исследовательские работы, сотрудничество с научно-исследовательскими институтами и турбостроительными заводами СССР, создание головных образцов мощных теплофикационных паровых турбин и газотурбинных установок, которые использовались для развития энергетики.

In this article the history of preparation of specialists in area of steam- and gas-turbines in the Kyiv Polytechnic Institute (end of XIX–XX centuries) is presented. The training of engineerings and scientific-pedagogical personnels, research works, collaboration with scientific-research institutes and turbine manufacture factories of the USSR, creation of brassboards of powerful introduction of a heating system steam-turbines and gas-turbine settings which were used for development of a power generation, had been described in it.
Keywords: подготовка кадров; подготовка профессиональная; турбины паровые; турбины газовые; инженер-педагог; энергетика; Kyiv polytechnic institute; specialist; training of personnels; steam-turbines; gas turbines